Usage theory of the plays for the plot value inquiry - Meszek, Wiesław (Technological and Economic Development of Economy, 2004)
With the plot value inquiry with the help of comparative worth procedure insecurity originates, in particular by the decision for the importance of the value‐influencing signs and the importance of the comparative prices. The play‐theoretical balance solution can play in the worth inquiry process an essential, complementary role, in particular as tools to the mistake and risk estimate. The shown procedure is based on the theory of the plays against the nature which had earlier only few practical interpretations.Article in German.Gleichgewichtbetrachtungen für die GrundstückswertermittlungLošimų teorijos taikymas žemės sklypo kainai nustatytiSantrauka. Nustatant žemės sklypo vertę palyginamuoju būdu kyla tam tikrų sunkumu dėl kaina veikiančiu veiksniu ir jų reikšmingumo. Lošimų teorija gali būti kaip svarbi papildoma priemonė, padedanti įvertinti klaidos ir rizikos galimybę. Pasiūlytas įvertinimo procesas pagrįstas “lošimų prieš gamtą” teorija, kuri ankstesnėje praktikoje buvo taikoma labai retai.First Published Online: 21 Oct 2010